An Analysis of Sick Leave in Sweden using Panel Data 1985-1997 - Curt Wells; David Edgerton; Agneta Kruse (Lund University, School of Economics and Management, Department of Economics, 2004)
Since the beginning of the 1990's, sick leave benefits accruing from the tax-financed Swedish social security insurance have been reduced a number of times. In this paper we use data from the survey on the Household Market and Non-market activities to estimate a fixed effects negative binomial model. We find a direct relationship between the rate of compensation and the amount of sick leave taken
Keywords: C23; C25; J22; 330; Sick insurance; sick leave compensation; panel data; fixed effects negative binomial